(untitled) (Journal of Geography and Environmental Management, 2020)
The article studies the physical and chemical properties, mechanical composition, and mode of the elements of the Akdala massif irrigated land. The mechanical composition of the soils of the Akdala massif was studied by the method of N. A. Kachinsky, the obtained data show the presence of silt in all layers. Data on the differentiation of fine mechanical elements on the capacity of cation exchange and factors contributing to the reduction of their fertility are presented. The study of the physical and chemical composition and chemical properties of the soils under consideration shows decrease in the humus content in the arable and sub- arable horizons. Long-term use of carbonate gray soils on arable land has led to a decrease in the content of organic substances and changed in the qualitative composition of humus substances. The study results of the agrochemical composition of rice crop rotation soils indicates that phosphorus levels are low and medium. Studies of mobile potassium show that the content of mobile potassium fully ensures the growth and development of plants. The most important nutrient for rice culture is nitrogen, which depends on the content of organic substances and staying in low place. According to the ecological and land reclamation conditions for studying the soils of the object, secondary salinization, salinization, waterlogging, long-term irrigation, irrational use of rice fields, have led to a deterioration in the physical and chemical properties of soils.